JHET INTERVIEWS: ROBERT F. HÉBERT. Issue 1 (March 2021) - Mosca, Manuela
Abstract : Robert F. Hébert was the eighteenth president of the History of Economics Society, from 1991 to 1992. He studied at Louisiana State University at Baton Rouge from his undergraduate degree (completed in 1965) to his PhD (obtained in 1970). During his academic career he taught economics in the US at Clemson University (South Carolina, 1970 to 1974), Auburn University (Alabama, 1974 to 2000), and the University of Louisiana at Lafayette (2000 to 2005); and in France at Université de Paris 1 (Sorbonne, 1995) and at the University of Caen (2004). Currently Professor Hébert is Russell Foundation Professor of Economics (Emeritus Professor of Entrepreneurial Studies) at Auburn University, and he resides in Baton Rouge, Louisiana. This interview was done in writing from November 6 to December 18, 2019.